The Theory of Canonical Moments with Applications in Statistics, Probability and Analysis - Rukhin, Andrew L. (Journal of the American Statistical Association, 1998)
Rukhin reviews "The Theory of Canonical Moments With Applications in Statistics, Probability and Analysis" by Holger Dette and William J. Studden.